(untitled) (LEARNing Landscapes, 2010)
In this essay, I discuss poetry as an important style of thinking and exploration. Poetry, I maintain, is a leap, a risk, a gambit that opens unexpected linguistic possibilities and imaginative opportunities. Based on my own experience of teaching poetry, I suggest strategies in this essay for encouraging students to take the kinds of risks that engender sense and confront nonsense. The central claim of this essay is that by creating new and surprising associations, poetry teaches us different and more interesting ways to live in and understand the world.